Emotion Processes Predicting Outbursts and Functional Impact in Misophonia - Wang, Qiaochu; Vitoratou, Silia; Uglik-Marucha, Nora; Gregory, Jane (Frontiers in Psychology, 2022)
Misophonia involves a decreased tolerance to certain sounds and is associated with a range of emotions and emotion processes. In addition to the distress caused by misophonia, some individuals report having aggressive outbursts and significant impact on doing things they would like to be able to do. This study aimed to examine whether misophonia-specific cognitive and emotional processes were associated with misophonic outbursts and impact, and whether these relationships could be explained in part by emotion processes not specific to misophonia. A sample of 703 individuals, 315 of whom identified with having misophonia, completed measures of misophonia, depression and anxiety symptoms, anxiety and disgust sensitivity, interoception, and beliefs about emotions. Exploratory correlation and regression analyses were used to build mediation models, which were tested using multiple linear regression. Externalising appraisals (blaming others for causing one’s reaction to sounds) was positively associated with misophonic outbursts, and this relationship was partially explained by anxiety symptoms and disgust sensitivity. Sense of emotional threat in misophonia predicted impact of misophonia, and this was partially explained by depression symptoms and negative beliefs about emotions. Anxiety sensitivity and interoception were not significant independent predictors of misophonic outbursts or impact. These results provide support for the relevance of emotion processes in misophonia and highlight the importance of using multi-dimensional measures of misophonia to improve our understanding of the condition.